A Case Report of an Adenomatoid Tumor of the Uterus Mimicking an Endometrioid Adenocarcinoma on Endometrial Curetting: a Diagnostic Pitfall. Issue 6 (July 2020) - Mhawech-Fauceglia, Paulette; Samroa, Damanzoopinder
Abstract : Adenomatoid tumors (AT) arising in the female genital tract are usually incidental findings occurring most often in the fallopian tube and uterine serosa and rarely in the myometrium. In the myometrium, they appear grossly as deep seated, small, firm, ill circumscribed nodules mimicking leiomyoma. Histologically they show a glandular and invasive pattern making well-differentiated/low-grade endometrioid adenocarcinoma a major differential diagnosis. However, this differential is rarely encountered in practice because myometrial AT is usually seen on the hysterectomy specimen, because of their anatomic position in the deep myometrium, and only rarely in endometrial curettings. Our case is the first to report an AT, which presented as a polyp with associated fibroid on hysterescopic examination. Microscopically, the endometrial curetting and myomectomy showed irregular glands and cystic structures with occasional cytokeratin positive single signet-ring like cells invading into the myometrium, features consistent with low-grade endometrioid adenocarcinoma. On hysterectomy specimen, there was an ill-defined 5 cm mass in the myometrium with protrusion into the endometrium. The morphology was similar to that seen in the endometrial curetting. A larger panel of immunostains was done and the neoplastic cells were positive for AE1/3, CK7, CAM5.2, calretinin, and D2-40 and negative for CD34. A diagnosis of AT was rendered and no further treatment was required. Although AT is rarely seen in endometrial curetting, they should be in the differential diagnosis of glandular lesions to avoid pitfalls and unnecessary management especially in young patients desiring fertility.